Cognitive behavioral therapy for insomnia in neurodegenerative disorders—targeting sleep disturbances in Alzheimer’s and Parkinson’s disease: a scoping review - Latella, Desirèe; Calderone, Andrea; Casella, Carmela; De Luca, Rosaria; Gangemi, Antonio; Impellizzeri, Federica; Caliri, Santina; Quartarone, Angelo; Calabrò, Rocco Salvatore (Frontiers in Psychology, 2025)
IntroductionInsomnia is highly prevalent in neurodegenerative disorders, yet pharmacological options carry safety and tolerability concerns. This scoping review mapped contemporary evidence for cognitive behavioral therapy for insomnia (CBT-I) across Alzheimer’s disease (AD), mild cognitive impairment (MCI), and Parkinson’s disease (PD).MethodsFollowing a preregistered protocol (OSF DOI: 10.17605/OSF.IO/8VP3F), we searched PubMed, Cochrane Library, Web of Science, and Scopus for studies published 2015–2025. We screened English-language studies in adults and applied dual independent review with consensus resolution. Of 105 records, 70 were screened after de-duplication, and 8 met eligibility criteria.ResultsAcross randomized trials, pilot and feasibility studies, and single-case experimental designs, CBT-I—delivered in person or via telehealth—consistently reduced insomnia severity and improved sleep quality, with frequent ancillary gains in mood, anxiety, and daytime functioning. Remote and digitally augmented delivery appeared feasible and acceptable for cognitively vulnerable adults and caregivers. Early signals suggested potential cognitive benefits in prodromal populations (AD/MCI), and exploratory observations linked improved sleep with plausible neurobiological mechanisms such as amyloid-beta dynamics. In PD, findings aligned with a mechanistic pathway in which presleep cognitive arousal, safety behaviors, and dysfunctional sleep beliefs are modifiable targets. Non-pharmacological comparators (e.g., mindfulness, therapeutic exercise, neuromodulation) also showed benefits, helping contextualize where CBT-I may offer disorder-relevant leverage on insomnia outcomes.DiscussionThe overall strength of evidence is tempered by small samples, heterogeneity in comparators and dosing, short follow-up, and inconsistent reporting of clinically meaningful change. Priorities include multicenter randomized trials with standardized sleep and cognitive endpoints, longer observation, head-to-head comparative effectiveness with economic evaluation, adaptive protocols tailored to PD-specific disruptors, and mechanistic studies integrating digital phenotyping and biomarkers to test durability and downstream clinical impact.